EXTRANET AND THEIR IMPLEMENTATION - Danang Nur Pratomo; Irwan Nimara, Ir, MM (Jurnal Sistem Komputer, 1998)
Extranet is in fact an implementation of internetworking technology to provide interoperabilitythroughout the ranks of the organization. In other words extranet is anInternet with an Internet connection has been modified so that it can be accessed bypersons outside of the various layers.The fourth chapter provides an introduction to the concepts underlying the extranet,provides an introduction to the extranet. Explaining the difference extranet with thekinds of other internetworking, and discusses the physical and logical architecture inwhich the extranet is built. Supported by the implementation of extranet in the realworld. Such as improving networking functions with other extranet.